Human immune responses to schistosoma japonicum recombinant and native antigens - Acosta, Luz Pablo (Thesis (DrPH, Parasitology)--University of the Philippines, Manila, 1999)
Cellular and humoral responses to specific S. japonicum recombinant and native antigen investigated in a well-defined study population of 155 individuals who belonged to a previous intensive water contact study in Jaro, Leyte. Population exposure and reinfection patterns were described based on available data from a e-year study of water contact observation and yearly reinfection after treatment. In this study, an attempt was made to categorically identify putative ?resistant? individuals whose relative lack of reinfection after yearly treatment could not be attributed to a lack of exposure. Peripheral blood mononuclear cell proliferation, cytokine (IFN-u, IL-5 and IL-10) production and antibody isotypic responses to defined recombinant and native antigens were measured. The antigens that were tested include the following recombinant antigens: 97 kDa full-length paramyosin (rPMY), 22 kDa tegumental antigen (rTEG), 14 kDa fatty-acid binding protein (rFABP); a 37 kDa glyceraldehyde-3-phosphate dehydrogenase (Rrapdh) and 28 kDa gluthathione-S-transferase (Rgst28). Immune responses to native soluble worm extracts (SWAP) and egg antigens (SEA) were also measured. Specific immune responses to these antigens were tested for possible relationships with several epidemiological parameters such as age, sex, exposure and infection intensity. Particular antigen-specific immune response among ?resistant? or ?susceptible? individuals were also assessed with the aim to associate and describe the immune response that these individuals have toward the antigens.
Consistent with earlier studies done in this community, analysis of exposure and reinfection data indicated possible development of acquired resistance observed at mid to late teens (age group 15-19). Immunological responses to the recombinant and native antigens suggest that both Th1 and Th2 type immune responses appear to be important in predicting resistance in this population. Consistently, high responses to SWAP were seen for both cellular and humoral responses. Of the five recombinant antigens tested, rPMY induced significant levels of IFN-y. Of importance was the evidence found for SWAP and rPMY induced IFN-y responses in predicting ?resistance?. It was noted that this association was significant even after the effects of age and sex were accounted for in multivariate analysis. Analysis of the study population also showed that females appear more likely to be resistant than males. On the other hand, specific antibody isotypes that were suggested in protection were IgE response to SWAP among females below 20 years of age (5-19) and IgA response to SWAP in the younger age groups (5-19). Compatible with other studies, IgM reactivities to SWAP and SEA and IgG4 response to rPMY among those at age groups (5-19) predicted ?susceptibility?. In this study, rPMY induces IFN-y production, a response that is significantly associated with resistance in this population, while there are also some indications that IgE and IgA response to SWAP may be important in inducing protection in human schostosomiasis japonica.
Keywords: Schistosomiasis